2003
DOI: 10.1159/000071969
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Repair of Gastroschisis in Fetal Rabbits

Abstract: Objective: Infants with gastroschisis (GS) still face severe morbidity. Prenatal closure may prevent gastrointestinal organ damage, but intrauterine GS repair (GSR) has not been established yet. Methods: In New Zealand White rabbits we developed and compared GS versus GSR: creation of GS was achieved by hysterotomy, right-sided laparotomy of the fetus and pressure on the abdominal wall to provoke evisceration. GSR was accomplished by careful reposition of eviscerated organs and a running suture of the fetal ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
0
9
0
2
Order By: Relevance
“…70 Till et al successfully performed intrauterine GS repair, but only 2 hours after the creation of the defect. 71 Santos et al found significant differences in the intestinal nervous plexus of fetuses with GS, with decreased histologic acetylcholinesterase activity, and smaller and more numerous intestinal neuronal cells, suggesting that the transitory intestinal dysmotility seen in GS could be secondary to alteration in the maturation of the enteric nervous plexus. 72 Biard et al created the defect on 22 or 23 days of GA to study the pulmonary effects of GS but did not identify any effects on lung growth and maturation.…”
Section: Gastroschisis Model Surgically Created In Rabbitsmentioning
confidence: 99%
“…70 Till et al successfully performed intrauterine GS repair, but only 2 hours after the creation of the defect. 71 Santos et al found significant differences in the intestinal nervous plexus of fetuses with GS, with decreased histologic acetylcholinesterase activity, and smaller and more numerous intestinal neuronal cells, suggesting that the transitory intestinal dysmotility seen in GS could be secondary to alteration in the maturation of the enteric nervous plexus. 72 Biard et al created the defect on 22 or 23 days of GA to study the pulmonary effects of GS but did not identify any effects on lung growth and maturation.…”
Section: Gastroschisis Model Surgically Created In Rabbitsmentioning
confidence: 99%
“…An actual therapeutic intervention directly aimed at improving the intestinal damage and function is yet to be widely adopted. To date, either clinically or mostly only experimentally, a number of prenatal strategies have been proposed, such as amnioexchange, amniotic fluid dilution, prenatal steroid administration, induced fetal diuresis, nitric oxide donors, and even intra-uterine repair of the defect, all with quite modest results and some risks (64)(65)(66)(67)(68).…”
Section: Trascet For Abdominal Wall Defectsmentioning
confidence: 99%
“…This study showed that bowel exposure to amniotic fluid reduces intestinal motility and gastric contractility in the preterm rabbit fetus. The fetal rabbit model of GS has recently been used to demonstrate the feasibility of intrauterine repair of GS for the first time [163]. This short study only assessed fetal survival for 5 h after initial GS creation and therefore has not addressed the issue of long-term survival following intrauterine GS repair or if there is any reduction in intestinal damage following the procedure.…”
Section: Surgically Created Gastroschisis Modelsmentioning
confidence: 99%